PERSEPSI CREW DAN MANAJEMEN DALAM PENERAPAN ISM CODE BAGI KESELAMATAN PELAYARAN DAN PERLINDUNGAN LINGKUNGAN LAUT - Nurhasanah, Nina; Joni, Asmar; Shabrina, Nur (Proceeding SENDI_U, 2015)
About 80% shipwreck occurred by human error, human error is 75% due to the poor management system, it must bemade to the management system that is able to create a good and close cooperation between the management boardand land management. International Safety Management Code (ISM Code) is an international standard of safetymanagement regulations for the security and safety of the operation of the ship and the prevention of pollution of themarine environment established by the IMO Maritime Safety Council. Purpose ISM Code is to ensure safety at sea,prevent accidents and loss of human life and avoid damage to the environment, especially the marine environmentand as well as the loss of property. Companies must certify in writing its policy on maritime safety andenvironmental protection and ensure that everyone in the company know and understand it. But perception Crewand Application Management in the ISM Code For Maritime Safety and Marine Environment Protection can bedifferent if there is no good training and application of the management company. To that periodically companiesneed to conduct training on the prevention and prevention of disorders of the safety of shipping activities concernedShipping Company. To overcome and prevent safety, Shipping Company should have the facilities and equipment inaccordance with the provisions of the ISM Code.Keywords: ISM Code, Sailing, Maritime Safety, Marine Environment